Vaginal bacterial microbiome composition in women living with HIV in Meru, Kenya - Mutoro, Thomas Atenya; Mogere, Sophia; Kemunto, Celestine; Simam, Joan; Mwenda, Cynthia N. Mugo; Onyambu, Frank G. (African Journal of Science, Technology and Social Sciences, 2025)
The immune system status and the vaginal microbiome represent risk factors for hrHPV and women living with HIV are susceptible to persistent HPV infections. This study characterized the vaginal bacterial communities in women living with HIV in Meru. A cross-sectional study was conducted involving 38 women living with HIV at the Meru Teaching and Referral Hospital. Genomic DNA extraction and 16S rRNA amplification was carried out. Bioinformatic analysis was performed using R and Cutadapt was used to perform sequence quality control. We identified 6,481 bacterial taxa. Lactobacillus and Gardnerella were the most abundant genera in the study population. In conclusion, this study shows the status of vaginal microbiome in Kenyan women living with HIV. Follow up studies are recommended to include control group of HIV-negative women.